2016
DOI: 10.1111/ijd.13316
|View full text |Cite
|
Sign up to set email alerts
|

Nail alterations during pregnancy: a clinical study

Abstract: During pregnancy, cutaneous and appendageal alterations manifest and may cause concern in the subject. The nails may be affected by pregnancy. This study investigated the frequency and nature of nail changes occurring during pregnancy in 312 healthy, 18-40-year-old pregnant women in gestation weeks 16-40. After a routine obstetric examination at the obstetrics and gynecology clinic at the study institution, all subjects submitted to an examination of all fingernails and toenails. Only nail alterations that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
1
9
0
3
Order By: Relevance
“…Studies report that nail alterations occur in 2% to 40% of gravid women ( Erpolat et al, 2016 , Rathore et al, 2011 ). The most commonly occurring changes are leukonychia, onychoschizia, and ingrown toenails but increased nail growth, onycholysis, melanonychia, and subungual keratosis are also described ( Erpolat et al, 2016 , Ponnapula and Boberg, 2010 , Soutou and Aractingi, 2015 , Turcic et al, 2009 , Tyler, 2015 , Van Onselen, 2012 ).…”
Section: Mucosamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report that nail alterations occur in 2% to 40% of gravid women ( Erpolat et al, 2016 , Rathore et al, 2011 ). The most commonly occurring changes are leukonychia, onychoschizia, and ingrown toenails but increased nail growth, onycholysis, melanonychia, and subungual keratosis are also described ( Erpolat et al, 2016 , Ponnapula and Boberg, 2010 , Soutou and Aractingi, 2015 , Turcic et al, 2009 , Tyler, 2015 , Van Onselen, 2012 ).…”
Section: Mucosamentioning
confidence: 99%
“…Studies report that nail alterations occur in 2% to 40% of gravid women ( Erpolat et al, 2016 , Rathore et al, 2011 ). The most commonly occurring changes are leukonychia, onychoschizia, and ingrown toenails but increased nail growth, onycholysis, melanonychia, and subungual keratosis are also described ( Erpolat et al, 2016 , Ponnapula and Boberg, 2010 , Soutou and Aractingi, 2015 , Turcic et al, 2009 , Tyler, 2015 , Van Onselen, 2012 ). Benign, uniform, symmetrical hyperpigmentation of the multiple nails is reported during pregnancy with fading that occurs postpartum ( Bieber et al, 2017 ); however, irregular pigmentation with cuticle involvement should be referred to a dermatologist for evaluation of possible melanoma.…”
Section: Mucosamentioning
confidence: 99%
“…Studies conducted almost 60 years ago reported that pregnancy increased the growth rate of nails . Several studies conducted since then have also reported that pregnancy accelerates nail growth, with references to these earlier studies . In addition, it has also been reported that leukonychia, subungual hyperkeratosis, distal onycholysis, transverse grooves, softening, and brittleness in nails might be encountered during pregnancy …”
Section: Introductionmentioning
confidence: 93%
“…6,7 Several studies conducted since then have also reported that pregnancy accelerates nail growth, with references to these earlier studies. 8,9 In addition, it has also been reported that leukonychia, subungual hyperkeratosis, distal onycholysis, transverse grooves, softening, and brittleness in nails might be encountered during pregnancy. [9][10][11][12][13][14][15] Studies about the effect of pregnancy on the hair follicle, which is considered the analog of the nail unit, showed an increase in hair diameter and in the number of hair follicles evident during the anagen phase.…”
Section: Introductionmentioning
confidence: 99%
“…У некоторых женщин отмечаются продольные темные линии (меланонихия) [31] лечением кутикулы требует немедленного внимания дерматолога или онколога для исключения меланомы. При обследовании ногтей на руках и ногах у 312 женщин наиболее часто отмечалась лейконихия (24,4%), на втором месте были вросшие ногти на стопах и онихошизис (по 9,0%), ускорение роста ногтей замечено в 6,7%, подногтевой гиперкератоз в 4,2% случаев [36].…”
Section: придатки кожиunclassified